Enhancing Creative Thinking Skills and Technological Literacy through Project-Based Microteaching: A Study on Prospective Physics Teachers at UIN Raden Intan Lampung - Diani*, Rahma; Susanti, Agus; Widiawati, Nanda; Velina, Yessy (Jurnal Pendidikan Sains Indonesia, 2025)
This study explores the impact of project-based learning (PjBL) integrated with microteaching on the creative thinking skills and technological literacy of prospective physics teachers at UIN Raden Intan Lampung with a mixed methods approach. As the demands of 21st-century education emphasize the importance of these skills, it is critical to evaluate innovative teaching methods that address these needs. A quasi-experimental design was used, involving two groups: an experimental group taught using the PjBL microteaching model and a control group using conventional methods. Creative hhinking skills was assessed using torrance tests of creative thinking (TTCT), measuring fluency, flexibility, originality, and elaboration. Technological literacy was evaluated through a structured questionnaire assessing skills in technology use, understanding, and integration in learning contexts. Results revealed a significant improvement in both creative thinking skills and technological literacy in the experimental group compared to the control group. Specifically, the PjBL microteaching model was more effective in enhancing students' ability to generate diverse ideas and utilize technology effectively in educational settings. These findings suggest that integrating PjBL with microteaching can better prepare future physics educators for the technological and creative demands of modern teaching environments